2016
DOI: 10.1017/gmh.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of internet interventions for youth mental health in Vietnam

Abstract: Background.Despite high levels of mental illness, Vietnamese youth have limited access to mental health care. Internet interventions, evidence-based psychotherapy treatments delivered through the internet, have the potential to increase access to mental health for youth in Vietnam. This study explored the perceptions of youths and parents toward internet interventions for youth mental health.Methods.Four focus groups were conducted with youths (n = 20) and parents (n = 20) in Danang, Vietnam. The Technology Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
5
17
0
Order By: Relevance
“…After we introduced the website suckhoetre.vn to selected secondary schools in Cantho city, Vietnam, nearly all of the students visited the site at least once or twice a week, and most of them used the website just to read information, which suggests that this is a good approach to give students relatively easy access to information they need. These ndings are in line with a report from Hue city, Vietnam in which both parents and students anticipated that the Internet would be a useful source for obtaining and sharing information for young people in Vietnam (Sobowale, Nguyen, Weiss, Van, & Trung, 2016). Most of the youth in our study population had access to Internet at home and very often on a smartphone, which would provide the con dentiality they need.…”
Section: Discussionsupporting
confidence: 88%
“…After we introduced the website suckhoetre.vn to selected secondary schools in Cantho city, Vietnam, nearly all of the students visited the site at least once or twice a week, and most of them used the website just to read information, which suggests that this is a good approach to give students relatively easy access to information they need. These ndings are in line with a report from Hue city, Vietnam in which both parents and students anticipated that the Internet would be a useful source for obtaining and sharing information for young people in Vietnam (Sobowale, Nguyen, Weiss, Van, & Trung, 2016). Most of the youth in our study population had access to Internet at home and very often on a smartphone, which would provide the con dentiality they need.…”
Section: Discussionsupporting
confidence: 88%
“…With most of the studies reviewed being conducted in developed countries, digital responses to CYPMH seem unbalanced. Previous research [ 60 - 62 ] highlighted the paucity of access to DHIs in low- and middle-income countries. This inequality could be because of limited resources (both financial and human), shortage of skilled personnel, infrastructure problems leading to poor internet penetration and connectivity [ 63 ], or the absence of a specific CYPMH policy [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other research (in Vietnam) has shown that although people are not aware of the availability of internet-based interventions, they do express that such intervention would be useful, especially when incorporating psychoeducation and the possibility of sharing of information ( Sobowale et al, 2016 ). The same challenge also applied in our study in Indonesia, in that 95% of our participants were unaware of existing internet-based interventions but were willing to try using it.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the Technology Acceptance Model on e-health in LMICs showed that both perceived ease of use and perceived usefulness were important factors of e-health acceptance in the context of mental health (e.g. ( Hoque et al, 2017 ; Sobowale et al, 2016 ). Those studies provide evidence that e-health is acceptable to potential users in LMICs.…”
Section: Introductionmentioning
confidence: 99%